Letters of Pietro Aretino to Veronica Gambara – a Dialogue in the Form of an Epistle - Marija Mitić (Društvene i Humanističke Studije)
In the Italian literary tradition of humanism and the Renaissance, the epistle holds a special place as a genre that uniquely reflects the intellectual, cultural, and social currents of the period. This form of literary expression was often used for the exchange of ideas, discussion of artistic and literary matters, and for establishing or reinforcing social connections. Among the many prominent authors who engaged with the epistolary form, Pietro Aretino stands out, with his contribution to the development of Italian epistolography being undeniable. His epistles, especially those addressed to noblewomen, such as the writer Veronica Gambara, represent a valuable source for understanding the cultural and literary dynamics of Renaissance Italy. In these letters, the dialogical form allows for an in-depth exploration of literary poetics, turning the epistle into a platform for the affirmation of female literary creativity. Aretino’s epistles not only reveal the complexity of the relationship between authors and female writers but also highlight the importance of the role of women in intellectual circles of the time. These texts, rich in cultural content and stylistic features, provide a unique perspective on Renaissance literature and represent an inexhaustible source for further interdisciplinary research.